(untitled) (Alternautas, 2023)
Public space is an essential part of daily and political life in Latin America. Yet its potential is often restricted by narrow definitions of public space geographies and the politics of defining these. Bogotá, Colombia is a case in point. At the turn of the millennium, it was hailed as a model city for a new neoliberal urban planning and governance regime that sought to democratize urban life through public space expansion and recovery. What emerged instead were new and further entrenched forms of exclusion. Going beyond the period of the “urban miracle” Bogotá experienced in the late 1990s and early 2000s, this paper explores a post-neoliberal vision for a more equitable city pursued by mayor Gustavo Petro through an ideology of urban revitalization. This new vision, I argue, used local heritage rather than abstract universal citizenship to produce a more endogenous form of public space politics that provided a stronger foundation for democratization and pursuing the right to the city by allowing grassroots efforts to enact the right to assert the (ontological) order of things in the city.